ASSOCIATION OF DRUG RELATED PROBLEMS (DRPs) OCCURRENCE WITH CLINICAL OUTCOME IN ISCHEMIC STROKE PATIENTS - FIRDHA APRILLIA WARDHANI; ZULLIES IKAWATI; NANANG MUNIF YASIN (Majalah Farmaseutik, 2023)
Ischemic stroke is one of the main causes of death and disability in Indonesia and in the world whose prevalence continues to increase. One of the factors that increase disability in ischemic stroke patients is poor stroke management, and the incidence of DRPs plays a role in it. This study was conducted to determine whether there is a significant relationship between the incidence of DRPs in ischemic stroke patients, and the patient's clinical outcome, which is described by the patient's NIHSS status. It is known that NIHSS is an outcome parameter with the best accuracy and sensitivity compared to other outcome parameters. The study was conducted with a retrospective cross-sectional design, involving 111 samples sourced from the medical records of patients who met the inclusion criteria in the April-October 2021 period. The DRPs analyzed in this study were medication errors, the need for additional drugs, too low drug doses, and drug side effects occur. In this study, DRPs occurred in 88.2% of patients, with the most common type being the need for additional drugs in patients. This study found that the presence of DRPs in ischemic stroke patients, has the potential to increase the risk of patients experiencing clinical outcomes that do not improve as described by the NIHSS status (OR 3,714; p-value<0,05).